An Introduction to Camphill Communities and the BA in Curative Education - Norma Hart; Angelika Monteux (Scottish Journal of Residential Child Care)
Curative Education is a multi-disciplinary, professional approach concerned with the physical, emotional and spiritual well-being of children and adults with special/complex needs. It encompasses care, education, craft and artistic activities and a medical, therapeutic element.